Land Value Capture sebagai Inovasi Pembiayan Non Pemerintah di Kota Pekalongan - Pradoto, Wisnu; Safrul, Muhammad; Anam Ramli, Nurul (JURNAL LITBANG KOTA PEKALONGAN, 2024)
The land use pattern and infrastructure investment serve as tools that can be utilized to create opportunities for increasing land economic value. This research aims to formulate the Land Value Capture (LVC) model as a non-governmental financing source that can be used to finance the development of the Pekalongan City Station area with the concept of Transit-Oriented Development (TOD). The analytical tools used include descriptive and literature studies, as well as SWOT analysis. The research area is focused on 3 (three) areas that may be ready for LVC implementation, namely 1) the Hoegeng Stadium area, 2) the former Sri Ratu area, shops on the east side, and 3) shops on the east side of the station. LVC instruments that can be applied in this area include land value taxes, joint development, land readjustment using diversification strategies. Keywords: Land Value Capture (LVC), Pekalongan City Station, Transit Oriented Development (TOD)